Green cooperative communication techniques for intelligent transportation systems - Vinod Kumar, Mogadala (2017)
The current scenario of transportation infrastructure demands the need for developing efficient intelligent transportation systems (ITS) because of the increased population, changes in population density, traffic congestion, etc. Recent literature on ITS discuss on the need for green cooperative diversity techniques to improve the energy efficiency of the wireless nodes which are embedded in the transportation infrastructure. In the present work, we propose single-input-multiple-output (SIMO) and spatial modulation (SM) techniques for multiple antenna cooperative ITS in order to improve the energy efficiency of wireless nodes. Moreover, the symbol error probability (SEP) performance and energy efficiency of the proposed techniques are analyzed and compared with the traditional techniques. From the simulation results, it has been inferred that energy efficiency of cooperative ITS can be improved by employing SIMO technique, whereas both energy and spectral efficiency improvement can be obtained by employing SM technique.